Challenges in the adoption of sustainability information systems: A study on green IS in organizations - Kirchner-Krath, Jeanine; Morschheuser, Benedikt; Sicevic, Nevena; Xi, Nannan; von Korflesch, Harald F.O.; Hamari, Juho (International Journal of Information Management, 2024)
Economic, social and ecological sustainability presents one of the greatest challenges of our society. As a result, there is growing pressure on a variety of organizations to implement sustainability programs, such as inclusion training related to social sustainability, cost management programs related to economic sustainability, and perhaps most importantly, green (information) systems related to environmental sustainability. Not only is multi-faceted sustainability most beneficial to organizations at large, but also there are several categorical thresholds that organizations must meet in order to be certified. For these reasons, companies are increasingly adopting information systems (IS) for sustainability in their operations. Specifically, programs designed to influence employee motivation, attitudes, beliefs, and behaviors are gaining attention. While there is a long tradition of research on technology adoption, such sustainability systems harbor several new phenomena, both with respect to individual and organizational adoption. Therefore, in this study, we explore the challenges of adopting sustainability systems in organizational contexts. Using activity theory and innovation diffusion theory, and with technology adoption theory as the backdrop of our investigation, we conduct a qualitative field study in four small- and medium- sized companies. Using both theory-guided deductive and inductive interpretation phases, we illuminate adoption challenges through combined intersections of adoption stages (knowledge, persuasion, decision, implementation, and confirmation) and activity domains (subject, instrument, object, community, rules). We then shed light on the severity and importance of these challenges through an expert validation study with green IS experts. In discussing the challenges in light of motivational and green IS design, we posit four dilemmas in green IS adoption that arise from tensions in the specific context of sustainability in organizations. Our findings expand existing knowledge in research on green IS, motivational IS design and sustainable behavior change interventions and yield several theoretical and practical avenues for future inquiry and endeavour.<br
Keywords: Green IS; Sustainability; Gamification; Adoption; Motivation

Combating Procrastination with Information Systems: A Systematic Review on Design Approaches and Effects - Kirchner-Krath, Jeanine; Birnstiel, Sandra; Morschheuser, Benedikt (ECIS 2024 Research Papers, 2024)
Procrastination, the act of postponing important tasks despite knowing the negative consequences, poses considerable risks to mental and physical well-being. Traditional procrastination treatments are time-consuming and often have high entry barriers for those affected. Consequently, information systems (IS) have emerged as an innovative approach to provide both guided and self-directed procrastination treatment. This study consolidates academic literature on IS design approaches for addressing procrastination and juxtaposes them with traditional behavioral, cognitive, and social support interventions. We reveal how IS can effectively assist individuals in combating procrastination, and shed light on the role of motivational design affordances. Our findings show that IS designs primarily address procrastination through behavioral strategies, yielding positive results in enhancing task efficiency. Yet, significant opportunities remain to explore the capabilities of adaptive and tailored IS design for cognitive benefits, delve into social support designs for overcoming procrastination, and explore motivational design to support functional IS against procrastination with hedonic experiences.
Keywords: Procrastination; Health IS; Mental health; IS design; Motivational design

Design Implications for a Gamified Recycling House - Palmquist, Adam; Goethe, Ole; Krath, Jeanine; Rosenlund, Joachim; Helmefalk, Miralem (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2022)
This paper encircles explorative design research in a multiple stakeholder triple helix project concerning circular economy and household recycling. Design ethnography was employed to find implications for outlining a gamification artifact that would facilitate recycling behaviors. We collected our data during 27 weeks by attending two field sites: Site A, project stakeholder meetings and a participatory design workshop, and Site B, semi-structured interviews in the household stakeholders’ residences. Our thematic analysis of the sites’ collected ethnographic record extrapolated two specific categories: Stakeholder requirements and Gamification ruleset, together enfolding five key-themes and various sub-themes that could be used to inform the design of a gamification artifact aimed at recycling. Also, based on our research, we propose two research propositions regarding storytelling and understanding for further gamification design researchers to investigate.
Created from Fastlane, Scopus look-up
Keywords: Circular economy; Design ethnography; Gamification; Informing design; Interviews; Participatory design; Recycling; Stakeholder; Thematic analysis

Designing gamification and persuasive systems: a systematic literature review - Krath, Jeanine; von Korflesch, Harald F.O. (Proceedings of the 5th International GamiFIN Conference, 2021)
Gamification design has been an important issue for practitioners and researchers since the beginning of research on gamification. With the increasing divergence of gamification in diverse areas, various design principles have been proposed. Yet, existing reviews focus on the synthesis of scientific knowledge about the design process and specific design elements, neglecting the importance of guidelines and principles to make appropriate design choices in order to achieve the desired outcomes. Therefore, this systematic review identifies, analyzes, and categorizes 30 articles that propose design guidelines for gamification and persuasive systems from various application contexts to provide scholars and practitioners with an overview in designing gamified interventions. More than 60 different principles have been identified, which can be divided into user-oriented principles to achieve the intended behavior, system-oriented principles to ensure a hedonic user experience, and context principles. Since the results are primarily conceptual, further research is invited to investigate the effectiveness of different principles based on the context of application to further refine the recommendations for specific use cases of gamification.
Keywords: Gamification; Design; Persuasive Systems; Literature Review; Gamification Design

Designing gamification for sustainable employee behavior: Insights on employee motivations, design features and gamification elements - Krath, Jeanine; Morschheuser, Benedikt; von Korflesch, Harald F.O. (Proceedings of the 55th Hawaii International Conference on System Sciences, 2022)
Encouraging sustainable employee behavior is critical for companies in the face of increasing societal pressure towards sustainability. While gamification has been shown to influence employee behavior effectively, current attempts to design gamification for sustainability in the workplace largely neglect the importance of understanding personal factors and contextual characteristics. This work explores employees‘ motivations for sustainable behavior and expectations for design features through in-depth interviews with 27 employees from different SMEs. Our results show that many employees tend to be egoistically motivated, suggesting the design of appropriate narratives and individualistic-oriented design features. Employees expected utilitarian, hedonistic, and social design features that primarily serve to support them in achieving personal sustainability goals while highlighting that gamification at work should also integrate seamlessly with existing work routines. We contribute to gamification design research by discussing the particularities of the workplace sustainability context and shedding new light on involving users in gamification desig
Keywords: Gamification; CSR; Corporate Social Responsibility; employee behavior; sustainability; user-centered design; Gender

Designing tailored gamification: A mixed-methods study on expert perspectives and user behavior in a gamified app for sustainability at work - Kirchner-Krath, Jeanine; Klock, Ana Carolina Tomé; Morschheuser, Benedikt; Park, Solip; Legaki, Zampeta; von Korflesch, Harald F.O.; Hamari, Juho (Proceedings of the 7th International GamiFIN Conference, 2023)
The establishment of the Sustainable Development Goals (SDGs) has put the transition to a sustainable society on the global agenda. In this respect, gamification has gained increasing attention as a tool for companies to motivate employees to adopt sustainable behaviors. Specifically, adapting gamification design to the preferences and needs of individual users has been strongly advocated. However, knowledge of personalized gamification design is largely based on conceptual assumptions and self-reported preferences. It remains thus unclear whether actual behavior of different user types matches theoretical conjectures and how user typologies can drive successful gamification design in sustainability contexts. This work addresses this gap by evaluating the design of a gamified app for sustainability at work by comparing expert evaluation (n=10) and analysis of actual user behavior (n=37) of different Hexad player types over a two-month period. In juxtaposing expert opinions and user behavior, our results reveal that actual user behavior greatly differs from expert suggestions and theoretical assumptions. Our results contribute to future research on tailored gamification by questioning the current state of tailored design theory mainly driven by self-report and pointing to the relevance of the context and non-stereotypical approaches for future personalization efforts.
Keywords: Sustainability; tailored gamification; personalization; player types; behavior; Diversity

Does behaviour match user typologies? An exploratory cluster analysis of behavioural data from a gamified fitness platform - Krath, Jeanine; Palmquist, Adam; Jedel, Izabella; Barbopoulos, Isak; Helmefalk, Miralem; Munkvold, Robin Isfold (Proceedings of the 6th International GamiFIN Conference, 2022)
A promising solution to increase user engagement in gamified applications is tailored gamification design. However, current personalisation relies primarily on user types identified through self-reporting rather than actual behaviour. As a novel approach, the present study used an exploratory machine learning analysis to identify seven clusters of users in a gamified fitness application based on their behavioural data (N = 19,576). The clusters were then conceptually compared to common user typologies in gamification, identifying possible relationships between behavioural user clusters and user types motivated by achievement, sociability, and extrinsic incentives. The findings shed light on nuanced behaviour patterns of user types in the fitness context and how knowing these patterns can inform the way in which tailored gamification could be implemented to meet the needs of specific types. Thereby, they contribute to the discussion on utilising behavioural data and user typologies for tailored gamification design.
Keywords: Cluster analysis; user types; tailored gamification design; personalisation; fitness; exploratorymachine learning; k-means clusterin

Everywhere but Nowhere: Development Experiences of the International Game Developers in Finland during the Covid-19 Pandemic and Remote Work - Park, Solip; Kultima, Annakaisa; Lehtonen, Miikka J.; Krath, Jeanine (Proceedings of the ACM on Human-Computer Interaction, 2022)
The Covid-19 pandemic has influenced people's views on work, and a significant portion of the global game industry converted to remote work during the pandemic. To explore the status of game development in this pivotal moment, we have conducted semi-structured interviews with 27 immigrant/expatriate game developers ("game expats") in Finland analyzing their migration push and pull on societal, industrial, social, and individual factors. The results indicate societal and industrial factors simultaneously influencing game expats' migration intention, but with an increasing influence of game corporation's role on developers' both on-the-job and off-the-job embeddedness due to an absence of (local) community activities during the pandemic. The data also reveals that game developers are valuing the physical workspace for face-to-face interactions, despite the industrial norm of digital tools and seamless transition to remote work. Furthermore, an alarming stratification and hierarchization within the game industry were identified, which game developers self-dividing in-house versus outsourced workforce even if they were both required to work remotely. This paper contributes to game studies on game developers' experiences as an attempt to investigate the local context of game development. It is also one of the first snapshots of game work practices in Finland during the Covid-19 era.
Created from Fastlane, Scopus look-up
Keywords: COVID-19; development experience; expatriation; game developers; remote work

Exploring the dark side of multiplayer online games: The relationship between contact experiences and sexism - Kordyaka, Bastian; Krath, Jeanine; Laato, Samuli; Park, Solip; Jahn, Katharina; Niehaves, Björn (AMCIS 2022 Proceedings, 2022)
The virtual communities of PC and console-based Multiplayer Online Games (MOGs) such as Fortnite or League of Legends continue to grow in popularity and attract millions of players around the world. Despite numerous enjoyable outcomes, some concerns have emerged regarding toxic player behavior such as sexism towards female players. In this study, based on the social identity approach and the contact hypothesis, we adopt the perspective of male players to examine the relationships between positive and negative contact and benevolent and hostile sexism in MOGs. We tested our proposed research model with data from 116 male players. In our sample, negative intergroup contact increased both measured forms of sexism (benevolent and hostile), whilst positive intergroup contact had no impact on either, partially confirming predictions from the contact hypothesis. Our work contributes to the discussion on intervention strategies to curb sexism in all its forms in MOGs.

Exploring the Relationship Between Offline Cultural Environments and Toxic Behavior Tendencies in Multiplayer Online Games - Kordyaka, Bastian; Park, Solip; Krath, Jeanine; Laato, Samuli (ACM Journal on Educational Resources in Computing, 2023)
In multiplayer online games, players from different cultural backgrounds come together to cooperate and compete in real time. Although these games are enjoyed by billions of players globally, behavioral issues such as toxic behavior (TB) have become rampant in some games, perhaps most infamously in multiplayer online battle arena (MOBA) games, such as League of Legends and Dota 2. A crucial step in curbing TB lies in understanding its drivers and antecedents. In the present work, we contribute to this field of research by considering the regional offline cultural environment in which players live. We draw both on Hofstede's Cultural Dimension Framework and on Kordyaka et al.’s Unified Theory of Toxic Behavior (UTTB) to compare two cross-sectional samples of MOBA players: one from North America (n = 155) and one from India (n = 119). Our analysis reveals significant differences between the samples for all UTTB variables. Additional analyses also indicate the relevance of national culture in relation to other dispositions (i.e., age) and characteristics (i.e., game-related culture). Our findings underscore the role that the offline cultural environments play in TB in MOBAs and additionally open avenues for further research that takes dimensions of national culture in the study of online behavior into account.<br

Gameful systems for corporate sustainability: systematic review, conceptual framework and research agenda on gamification and sustainable employee behavior in companies - Kirchner-Krath, Jeanine; Dijkstra-Silva, Samanthi; Morschheuser, Benedikt; von Korflesch, Harald F.O. (Internet Research, 2024)
Purpose Given the urgency of corporate engagement in sustainable development, companies seek ways to involve their employees in sustainability efforts. In this regard, gamified systems have gained attention as a novel tool to promote sustainable employee behavior. However, as the research field matures, researchers and practitioners are confronted with a scattered academic landscape that makes it difficult to grasp how gamification can be designed to engage employees in sustainable behavior and to understand how gamification effects unfold at psychological, behavioral and corporate levels of sustainability. Design/methodology/approach This paper uses a systematic literature review to consolidate the existing knowledge on gamification designs and their effects on sustainable employee behavior. Findings Studies have explored a variety of utilitarian and achievement-, immersion- and social-related gameful affordances to promote positive behavior- and system-related psychological effects as a basis for employee engagement in sustainable behavior. However, the evidence regarding their impact on rational decision-making processes and overcoming the intention-action gap inherent in sustainability is still limited. Nevertheless, several studies in focused areas indicate the potential to elicit behavioral changes that drive sustainability outcomes at the corporate level as well. Originality/value Our study provides three main contributions. First, we develop a conceptual framework that illustrates how gamification can drive sustainable behavior in the workplace. Second, we derive seven agenda points to guide future research on gamification for corporate sustainability. Third, we deduce three practical approaches to use gamification as a strategic intervention to promote sustainable behavior in organizations.
Keywords: Gamification; Serious games; Sustainble employee behavior; Pro-environmental behavior; Green behavior; Green IS; Motivational IS; Digital sustainability; Corporate sustainability; Corporate social responsibility; Sustainable development

Gamification for Sustainable Employee Behavior: A Design Science Research Study - Kirchner-Krath, Jeanine (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)
With the increasing importance and urgency of climate change, companies are challenged to contribute to sustainable development, especially by younger generations. However, existing corporate contributions have been criticized as insufficient, which could be particularly caused by a lack of employee engagement in corporate sustainability. In this context, gamification has been proposed and increasingly investigated in recent years as a promising, innovative tool to motivate sustainable employee behaviors in the workplace. However, there are few studies and applicable gamification solutions that address more than one specific sustainability issue and thus take a holistic perspective on sustainable behaviors in the workplace. Moreover, previous research lacks a comprehensive understanding of how different gamification elements elicit specific psychological effects, how these manifest in behavioral changes, and how these, in turn, cumulatively result in measurable corporate outcomes. The path from gamification as ”input” to corporate sustainability as ”output” thus remains unexplored. This dissertation fills this gap by conceptualizing, designing, and evaluating a holistic gamified intervention that supports employees in various sustainable behaviors in their daily activities. The project uses a design science research approach that closely involves employees in the incremental development of the solution. As part of the iterative design process, this dissertation presents six studies to extend the theoretical understanding of gamification for sustainable employee behaviors. First, a comprehensive review of existing research on gamification for sustainable employee behavior is provided, analyzing gamification designs and results of previous studies and outlining an agenda for further research (Study 1). Theoretical foundations of research on gamification, serious games, and game-based learning (Study 2) and empirical design principles for gamification and persuasive systems (Study 3) are then systematically reviewed as a basis for the successful design of gamified applications. Subsequently, empirical studies explore employees’ motivations for sustainable behavior and illuminate their expectations for design features (Study 4), and identify contextual challenges and design dilemmas when implementing gamification in an organizational context (Study 5). Finally, a quantitative field study (Study 6) explores how different gamification designs influence sustainable employee behavior and corporate sustainability in organizations. Based on the findings, this dissertation presents a comprehensive framework of gamification for sustainable employee behavior that incorporates design, individual behavior, and organizational perspectives. Finally, building on these insights, it provides practical recommendations for designing gamification to encourage sustainable employee behavior at work.<br

Gamification for sustainable employee behavior: Extended Abstract for the CHI PLAY 2021 doctoral consortium - Krath, Jeanine (CHI PLAY 2021 - Extended Abstracts of the 2021 Annual Symposium on Computer-Human Interaction in Play, 2021)
Created from Fastlane, Scopus look-up
Keywords: Design; Gamification; Organizational Behavior; Sustainability

Gamification: Motiviertes Lehren und Lernen spielend leicht gemacht - Schürmann, Linda; Kirchner-Krath, Jeanine; von Korflesch, Harald F.O. (Digitalisierung in der Schule. Ein Praxisbuch zu Möglichkeiten, Grenzen und Herausforderungen, 2024)
Spielen und Lernen sind seit jeher eng verbunden. Kinder erkunden spielend ihre Umwelt und testen hierbei ihre Grenzen aus. Sie üben dadurch beispielsweise schon früh, sich in die Perspektiven verschiedener Personen (Mama, Papa, Kind) hineinzuversetzen (z. B. Mead 2015). Den Drang zum Spiel und zur Exploration teilen alle Menschen und auch Erwachsene spielen – viele von ihnen oft und gerne. Friedrich Schiller geht in seiner ästhetischen Erziehung gar soweit, das Spielen zum prototypisch menschlichen Verhalten zu erklären: „Der Mensch spielt nur, wo er in voller Bedeutung des Worts Mensch ist, und er ist nur da ganz Mensch, wo er spielt“ (Schiller, Über die ästhetische Erziehung des Menschen). Sie lernen dabei zum Beispiel in Rollenspielen ganz nebenbei und unabsichtlich die Namen und Fähigkeiten von hunderten Spielcharakteren, ohne diese ein einziges Mal bewusst auswendig zu lernen. Was wäre, wenn wir diese Effekte transferieren könnten, zum Beispiel auf das Lernen von Vokabeln? Das Forschungs- und Anwendungsgebiet Gamification beschäftigt sich genau mit dieser Frage und zeigt auf, wie das Potenzial, das in unserem Spieltrieb schlummert, genutzt werden kann, um Lehren und Lernen ansprechender, einfacher und erfolgreicher zu gestalten.<br

Hexad-12: Developing and Validating a Short Version of the Gamification User Types Hexad Scale - Krath, Jeanine; Altmeyer, Maximilian; Tondello, Gustavo F.; Nacke, Lennart E. (Conference on Human Factors in Computing Systems - Proceedings, 2023)
The Hexad scale is a crucial tool for personalized gamification in user experience (UX) design. However, completing a 24-item questionnaire can increase dropout rates and screen fatigue within online surveys. When included in larger surveys, scale brevity makes a difference. To reduce the time required for the assessment process, we developed and validated a 12-item version of the Hexad scale. To create it, we carried out an exploratory factor analysis on an existing data set to identify appropriate items (n = 882). To validate the 12-item version, we conducted a confirmatory factor analysis on a new data set (n = 1, 101). Our results show that Hexad-12 outperforms the original Hexad scale regarding model fit, reliability, convergent, and discriminant validity. Therefore, Hexad-12 resolves issues found in studies using the original Hexad scale and provides a suitable and swift instrument for concisely assessing Hexad user types in tailored gamification design.
Created from Fastlane, Scopus look-up
Keywords: Adaptive Gamification; Gamification; Hexad; Personalization; Player Types; Tailored Gamification; User Types

How to increase sustainable engagement in the workplace through green IS: The role of instructional and motivational design features - Krath, Jeanine; Morschheuser, Benedikt; von Korflesch, Harald F.O.; Hamari, Juho (ECIS 2023 Research Papers, 2023)
Research on green IS has emphasized the value of both instructional and motivational elements in supporting sustainable behavior at work. However, there is still a lack of understanding of these different feature types' individual roles and relevance in inducing sustainable employee behavior. Our study addresses this gap and investigates the use and effects of different instructional and motivational elements in a green IS through a field study with 92 employees in five companies. Our findings based on the analysis of behavioral data shows that instructional elements are more relevant in inducing sustainable behavior, but motivational elements can amplify the positive influence of instructional elements, in particular for long-term user engagement. We contribute to theory and practice by revealing the role of instructional and motivational elements in the successful design of green IS for sustainable employee behavio
Keywords: Green IS; Sustainable behavior; Sustainable employee behavior; Motivation; Learning; Gamification

Leaf your Chair Behind - Calm Persuasion for Frequent Sitting Breaks Among Office-Workers - Jung-Krenzer, Theresa; Kirchner-Krath, Jeanine; Retz, Celina; Altmeyer, Maximilian (ACM International Conference Proceeding Series, 2024)
Sedentary behavior has been linked to numerous detrimental health outcomes. This is particularly pronounced among office workers. Sitting breaks can attenuate some of these detrimental health effects. Thus, our goal was to design a persuasive system to prompt frequent sitting breaks in the office. With our system we want to address two key issues of existing approaches: low compliance due to lack of motivation, and user annoyance with frequent prompts. Based on a literature review, we developed four design concepts each using a different prompt modality (appearance, audio, light, movement) and evaluated them qualitatively by conducting a focus group interview with a panel of workplace health management experts (N=5) and quantitatively in an explorative online study with our target demographic (N=39) rating the concepts' perceived persuasiveness and obtrusiveness. Based on our findings, we derive design implications for researchers and practitioners, and demonstrate their technical feasibility by providing a proof-of-concept implementation.
CRIS-Team Scopus Importer:2024-09-20
Keywords: calm technology; office; persuasive technology; sedentary behavior

Online Educational Escape Rooms – Ein Fallbeispiel - Hörsch, Hella; von Korflesch, Harald F.O.; Kirchner-Krath, Jeanine; Köhler, Jessica (Digitale Kulturen der Lehre entwickeln: Rahmenbedingungen, Konzepte und Werkzeuge, 2024)
Aufgrund der Covid-19-Pandemie haben virtuelle Lernformate an Bedeutung gewonnen. Insbesondere in der Hochschullehre werden innovative Methoden gesucht, um die Motivation und interaktive Einbindung von Student:innen zu fördern. In diesem Beitrag wird eine Fallstudie zu einem edukativen Online Escape Room an der Universität Koblenz-Landau vorgestellt. Das Masterseminar „Management und Führung“ mit N = 18 Student:innen und der Webdienst „Gather“ dienten als Basis. Mittels eines Mixed-Methods Ansatzes wurde evaluiert, ob der Lernerfolg, die intrinsische Motivation und die Kollaboration der Student:innen durch den Einsatz des Escape Rooms gesteigert werden konnte und wie die UX bewertet wurde. Neben den Ergebnissen werden Limitationen sowie Implikationen für die Hochschullehre diskutiert.<br

Outplay Your Weaker Self: A Mixed-Methods Study on Gamification to Overcome Procrastination in Academia - Kirchner-Krath, Jeanine; Schmidt-Kraepelin, Manuel; Schöbel, Sofia; Ullrich, Mathias; Sunyaev, Ali; von Korflesch, Harald F.O. (CHI '24: Proceedings of the CHI Conference on Human Factors in Computing Systems, 2024)
Procrastination is the deliberate postponing of tasks knowing that it will have negative consequences in the future. Despite the potentially serious impact on mental and physical health, research has just started to explore the potential of information systems to help students combat procrastination. Specifically, while existing learning systems increasingly employ elements of game design to transform learning into an enjoyable and purposeful adventure, little is known about the effects of gameful approaches to overcome procrastination in academic settings. This study advances knowledge on gamification to counter procrastination by conducting a mixed-methods study among higher education students. Our results shed light on usage patterns and outcomes of gamification on self-efficacy, self-control, and procrastination behaviors. The findings contribute to theory by providing a better understanding of the potential of gamification to tackle procrastination. Practitioners are supported by implications on how to design gamified learning systems to support learners in self-organized work.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Gameful design; Gamification; Higher education; Learning; Procrastination; Task management

Player Types and Game Element Preferences: Investigating the Relationship with the Gamification User Types HEXAD Scale - Krath, Jeanine; von Korflesch, Harald F.O. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2021)
Gamification has gained scientific attention as a motivational tool for behavior change in various contexts. When designing gamification, several scholars emphasize the importance of tailoring content to the needs of different users, e.g. by using the gamification user types HEXAD typology. From a theoretical point of view, researchers suggest correlations between HEXAD types and certain game elements, but empirical validation of these assumptions is still lacking. Previous studies show limitations either in terms of sample size or comprehensiveness of analysis. Therefore, this study aims to empirically identify game element preferences of different HEXAD types and to validate both the English and a corresponding German version of the HEXAD scale in a quantitative study design with 1,073 participants. The validation shows that the HEXAD scale is a valuable tool for identifying HEXAD types, with some improvements needed for a better model fit. Correlation analysis shows highly significant correlations between HEXAD types and specific game elements. While Philanthropists are motivated by gifting, administrative roles, and knowledge sharing, Free Spirits prefer creativity tools, exploratory tasks, and learning. Both Achievers and Players like challenges, leaderboards, levels, and competition, but Players are additionally attracted by extrinsic elements such as achievements, points, and rewards. Socializers like social elements, i.e., teams, social discovery, and social networks. Finally, Disruptors like anarchic gameplay and innovation platforms. In general, the results suggest that the HEXAD typology provides helpful and validated guidance for tailored gamification, and our findings should successfully drive future gamification design to maximize the desired behavioral outcome.
Created from Fastlane, Scopus look-up
Keywords: Game elements; Gamification; Gamification design; HEXAD; Player types; Tailored gamification; User types

Revealing the theoretical basis of gamification: A systematic review and analysis of theory in research on gamification, serious games and game-based learning - Krath, Jeanine; Schürmann, Linda; von Korflesch, Harald F.O. (Computers in Human Behavior, 2021)
Despite increasing scientific interest in explaining how gamification supports positive affect and motivation, behavior change and learning, there is still a lack of an overview of the current theoretical understanding of the psychological mechanisms of gamification. Previous research has adopted several different angles and remains fragmented. Taking both an observational and explanatory perspective, we examined the theoretical foundations used in research on gamification, serious games and game-based learning through a systematic literature review and then discussed the commonalities of their core assumptions. The overview shows that scientists have used a variety of 118 different theories. Most of them share explicitly formulated or conceptual connections. From their interrelations, we derived basic principles that help explain how gamification works: Gamification can illustrate goals and their relevance, nudge users through guided paths, give users immediate feedback, reinforce good performance and simplify content to manageable tasks. Gamification mechanics can allow users to pursue individual goals and choose between different progress paths, while the system can adapt complexity to the user's abilities. Social gamification elements may enable social comparison and connect users to support each other and work towards a common goal.
Created from Fastlane, Scopus look-up
Keywords: Gamification; Serious games; Game-based learning; Systematic review; Self-determination theory; Flow

Towards an Ethical Metaverse: A Systematic Literature Review on Privacy Challenges - Xie, Runjie; Kirchner-Krath, Jeanine; Morschheuser, Benedikt (ECIS 2024 Proceedings, 2024)
Along with the increasing interest in the metaverse as a new space for social interaction, privacy challenges that arise from new forms of data collection and usage have received notable research interest. Still, researchers and practitioners lack a structured overview of these privacy challenges as a foundation to explore measures that allow for safe and protected interaction in an ethical metaverse. To bridge this gap, we conducted a systematic literature review. We find that interaction in the metaverse carries the risk of revealing more sensitive personal data than in the traditional Internet. Moreover, we identify metaverse privacy challenges on different stakeholder levels, which often mirror those from the traditional Internet. Nevertheless, the metaverse also introduces novel facets to existing challenges due to its unique characteristics. These facets are discussed across six essential dimensions of privacy. Based on our findings, we provide recommendations for building a safe and secure metaverse environment.<br
Keywords: Metaverse; Extended Reality; Virtual World; Avatar; Privacy; Security; Literature Review.

Uncovering the theoretical basis of user types: An empirical analysis and critical discussion of user typologies in research on tailored gameful design - Kirchner-Krath, Jeanine; Altmeyer, Maximilian; Schürmann, Linda; Kordyaka, Bastian; Morschheuser, Benedikt; Klock, Ana Carolina Tomé; Nacke, Lennart; Hamari, Juho; von Korflesch, Harald F.O. (International Journal of Human-Computer Studies, 2024)
Gamification has become one of the main areas in information systems and human–computer interaction research related to users’ motivations and behaviors. Within this context, a significant research gap is the lack of understanding of how users’ characteristics, especially in terms of their preferences for gameful interaction (i.e., user typologies), moderate the effects of gamification and, furthermore, how gamification could be tailored to individual needs. Despite their prominence in classifying users, current typologies and their use in research and practice have received severe criticism regarding validity and reliability, as well as the application and interpretation of their results. Therefore, it is essential to reconsider the relationships and foundations of common user typologies and establish a sound empirical basis to critically discuss their value and limits for personalized gamification. To address this research gap, this study investigated the psychometric properties of the most popular player types within tailored gamification literature (i.e., Bartle's player types, Yee's motivations to play, BrainHex, and HEXAD) through a survey study (n=877) using their respective measurement instruments, followed by a correlation analysis to understand their empirical relations and an exploratory factor analysis to identify the underlying factors. The results confirm that user typologies, despite their different origins, show considerable overlap, some being consistent whereas others contradicted theoretically assumed relationships. Furthermore, we show that these four user typologies overall factor into five underlying and fundamental dimensions of Socialization, Escapism, Achievement, Reward Pursuit, and Independence, which could be considered common concepts that may essentially reflect key determinants of user motivation in gamification. Our findings imply that future research and practice in tailored gamification design should shift the focus from developing and applying ever more nuanced typologies to understanding and measuring the key underlying determinants of user motivation in gameful systems. Moreover, given the considerable interrelationships between these determinants, we also argue that researchers should favor continuous representations of users’ motivations in specific situations instead of a dichotomous operationalization of user types as static manifestations of their preferences.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Adaptive gamification; Game-based learning; Personalization; Player types; Serious games; Tailored gamification

Understanding toxicity in multiplayer online games: The roles of national culture and demographic variables - Kordyaka, Bastian; Krath, Jeanine; Park, Solip; Wesseloh, Henrik; Laato, Samuli (Proceedings of the 55th Hawaii International Conference on System Sciences, 2022)
Toxic behavior (TB) is a negative response to in-game frustration in multiplayer online games (MOG) that can ruin the playing experience, causing financial damage to MOG operators. Understanding the drivers of TB is an important step to curb the behavior. In this work, we consult the model of national culture (MNC) as well as demographic variables (e.g., education, gender, and age) as antecedent variables of TB using an exploratory design. We surveyed players of League of Legends and Dota 2 with two samples, based on the MNC, from North America (n=155) and India (n=119). We observed significant cultural differences in TB, with higher levels of self-reported toxicity in the Indian sample. In both samples, consistent with previous findings, age was negatively associated with TB. However surprisingly, there was a statistically significant difference among the two groups in terms of the relationship between education and TB.<br